Trk Receptors and Neurotrophin Cross-Interactions: New Perspectives Toward Manipulating Therapeutic Side-Effects - Haddad, Yazan; Adam, Vojtěch; Heger, Zbyněk (Frontiers in Molecular Neuroscience, 2017)
Some therapeutic side-effects result from simultaneous activation of homolog receptors by the same ligand. Tropomyosin receptor kinases (TrkA, TrkB and TrkC) play major role in development and biology of neurons through neurotrophins signaling. The wide range of cross-interactions between Trk receptors and neurotrophins vary in selectivity, affinity and functions. In this study we discuss new perspectives to manipulation of side-effects through understanding the cross-interactions at the molecular level by computational methods. Available crystal structures of Trk receptors and neurotrophins are valuable resource for exploitation via molecular mechanics and dynamics. Study of the energetics and dynamics will provide insight to structural regions that can be candidates for drug targeting and signaling pathway selection.